2001
DOI: 10.1021/bi001725i
|View full text |Cite
|
Sign up to set email alerts
|

Stability Studies of FhuA, a Two-Domain Outer Membrane Protein from Escherichia coli

Abstract: FhuA (MM 78.9 kDa) is an Escherichia coli outer membrane protein that transports iron coupled to ferrichrome and is the receptor for a number of bacteriophages and protein antibiotics. Its three-dimensional structure consists of a 22-stranded beta-barrel lodged in the membrane, extracellular hydrophilic loops, and a globular domain (the "cork") located within the beta-barrel and occluding it. This unexpected structure raises questions about the connectivity of the different domains and their respective roles i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
38
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 30 publications
(59 reference statements)
6
38
0
Order By: Relevance
“…In addition, ITC data indicated that, in vitro, MccJ25 binds to one single class of sites, with a stoichiometry consistent with two ligands per receptor (n = 1.9). By comparing the thermal denaturation profile of the MccJ25-FhuA complex with that of FhuA, which presents two transitions as characterized previously [20,28], we showed that MccJ25 binding affected only the external loops and plug (first domain) of FhuA, and not the β-barrel (second domain). Indeed, unfolding of the first domain required a much higher enthalpy when MccJ25 was associated with FhuA, indicating that stabilization of the first domain results from binding of MccJ25 to FhuA.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…In addition, ITC data indicated that, in vitro, MccJ25 binds to one single class of sites, with a stoichiometry consistent with two ligands per receptor (n = 1.9). By comparing the thermal denaturation profile of the MccJ25-FhuA complex with that of FhuA, which presents two transitions as characterized previously [20,28], we showed that MccJ25 binding affected only the external loops and plug (first domain) of FhuA, and not the β-barrel (second domain). Indeed, unfolding of the first domain required a much higher enthalpy when MccJ25 was associated with FhuA, indicating that stabilization of the first domain results from binding of MccJ25 to FhuA.…”
Section: Discussionsupporting
confidence: 55%
“…FhuA displays two well resolved thermal transitions, corresponding to the unfolding of the loops and plug, and to the unfolding of the β-barrel [20,28]. Under our experimental conditions, these were observed at 63 and 70 • C respectively ( Figure 5B).…”
Section: Affinity Constant For Binding Of Mccj25 To Fhuamentioning
confidence: 77%
See 1 more Smart Citation
“…(i) ␤-Barrel proteins are known for their remarkable stability. For instance, the ␤-barrels of FhuA of E. coli (22 ␤-strands) or Omp21 from D. acidovorans (8 ␤-strands) are stable up to 75°C and Ͼ80°C (40,41). It is interesting to note in this regard that the stability of the ␤-barrel against denaturation is not coupled to localization of those proteins in the outer membrane, since also soluble ␤-barrel proteins such as the lipocalins or green fluorescent protein show very high transition temperatures of 61 and 82°C, respectively (42,43).…”
Section: Figmentioning
confidence: 99%
“…Stability studies using differential scanning calorimetry experiments have shown the autonomous behavior of the cork and the ␤-barrel that unfold at different temperatures (12). The interactions between the cork domain and the ␤-barrel consist of nine salt bridges and more than 60 hydrogen bonds (11).…”
mentioning
confidence: 99%